Modeling and Simulation of a Baggage Handling System Based on AutoMod - LI Xiaojun; YANG Zhiyong; ZHANG Chunliang (Kongzhi Yu Xinxi Jishu)
To evaluate the performance of airport baggage handling system (BHS) prior to its establishment and implementation, this paper presented a three-dimensional visual model of a large airport BHS in China by using AutoMod simulation test platform. According to the simulation results of the model, the operational parameters and performance of the system were analyzed, and then the system design and operation were continuously improved and optimized. Final simulation model can be used as the basis of real operation analysis for the airport BHS.